THE REPRESENTATION OF BLACK WOMEN STRUGGLE IN MAYA ANGELOU’S POEMS “EQUALITY” - Siti Munawaroh; Pepi Siti Paturohmah (CALL, 2019)
This study analyzes the representation of Black women struggle in Maya Angelou’s poem. In this study, the researcher chose a poems of Maya Angelou. The poem entitles “Equality”. In order to discover the representation of black women struggle in those poems, the study was conducted by using intrinsic elements of poetry, feminist literary critic, gynocriticism and biography of Maya Angelou. This study was conducted into two research problem; 1. How Maya Angelou represent black women struggle in her poem? 2. What kinds of struggle does Angelou describe in her poem? The result of this study shows that Maya Angelou represent the struggle of black women through the intrinsic elements. She represent that there is a clash between black women and white people. White people treat black women in a bad way because they are consider black women as slave. The poems shows that black women struggle against racism.Keywords: Representation, black women, struggle, gynocriticism